2014
DOI: 10.3348/kjr.2014.15.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty of the Entire Thoracic and Lumbar Vertebrae for Vertebral Compression Fractures Related to Chronic Glucocorticosteriod Use: Case Report and Review of Literature

Abstract: Glucocorticosteroid-induced osteoporosis is the most frequent of all secondary types of osteoporosis, and can increase the risk of vertebral compression fractures (VCFs). There are promising additions to current medical treatment for appropriately selected osteoporotic patients. Few studies have reported on the efficiency of percutaneous vertebroplasty (PVP) or kyphoplasty for whole thoracic and lumbar glucocorticosteroid-induced osteoporotic vertebral compression fractures. We report a case of a 67-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…PVP and PKP may have less beneficial effects in glucocorticoid-induced osteoporosis (GIOP) than in primary osteoporosis as studies have shown that PVP and PKP might predispose patients to re-fracture through the shifting of the normal load transmission through the spine [28,29]. Tian et al [30] reviewed the literature regarding PVP or PKP in GC-related osteoporotic VCF from 1995 to 2013. One hundred and seventeen GIOP patients with VCF from 11 studies were included [30].…”
Section: Surgical Management Of Glucocorticoid-induced Osteoporotic Vcfmentioning
confidence: 99%
See 2 more Smart Citations
“…PVP and PKP may have less beneficial effects in glucocorticoid-induced osteoporosis (GIOP) than in primary osteoporosis as studies have shown that PVP and PKP might predispose patients to re-fracture through the shifting of the normal load transmission through the spine [28,29]. Tian et al [30] reviewed the literature regarding PVP or PKP in GC-related osteoporotic VCF from 1995 to 2013. One hundred and seventeen GIOP patients with VCF from 11 studies were included [30].…”
Section: Surgical Management Of Glucocorticoid-induced Osteoporotic Vcfmentioning
confidence: 99%
“…Tian et al [30] reviewed the literature regarding PVP or PKP in GC-related osteoporotic VCF from 1995 to 2013. One hundred and seventeen GIOP patients with VCF from 11 studies were included [30]. It was perceived that PVP was a safe and effective procedure for pain relief in selected patients with repeated and/or multiple thoracic-lumbar VCFs related to GCs.…”
Section: Surgical Management Of Glucocorticoid-induced Osteoporotic Vcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous vertebroplasty (PVP), as a minimally invasive, safe and effective technique, has gained wide clinical acceptance for the treatment of both primary and glucocorticosteroid-induced osteoporotic vertebral compression fractures 6–9. However, PVP for adjacent vertebral stress fracture with intervertebral pseudarthrosis formation due to AS is less known.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous vertebroplasty (PVP), as a minimally invasive, safe and effective technique, has gained wide clinical acceptance for the treatment of both primary and glucocorticosteroid-induced osteoporotic vertebral compression fractures. 6 – 9 However, PVP for adjacent vertebral stress fracture with intervertebral pseudarthrosis formation due to AS is less known. Recently, we have designed an innovative approach – percutaneous interbody fusion (PIF) – developed from PVP, which has not been reported in the literature thus far to our knowledge, especially for patients with adjacent vertebral stress fracture of AS with intervertebral pseudarthrosis formation.…”
Section: Introductionmentioning
confidence: 99%